Sleep disorders in myotonic dystrophy type 2: a controlled polysomnographic study and self‐reported questionnaires. (10th July 2013) - Romigi, A.; Albanese, M.; Placidi, F.; Izzi, F.; Liguori, C.; Marciani, M. G.; Mercuri, N. B.; Terracciano, C.; Vitrani, G.; Petrucci, A.; Di Gioia, B.; Massa, R.
<x xml:space="preserve">Abstract</x> Background and purpose There is a paucity of data available regarding the occurrence of sleep disorders in myotonic dystrophy type 2 (DM2). In this study the sleep–wake cycle and daytime sleepiness were investigated in DM2 patients and compared with results from healthy subjects and myotonic dystrophy type 1 (DM1) patients. Methods Twelve DM2 outpatients, 12 age‐ and sex‐matched healthy controls and 18 DM1 patients were recruited. Subjective quality of sleep was assessed by means of the Pittsburgh Sleep Quality Index (PSQI). Both the Epworth Sleepiness Scale and the Daytime Sleepiness Scale were performed in order to evaluate excessive daytime sleepiness (EDS). All participants underwent polysomnographic monitoring over 48 h as well as the Multiple Sleep Latency Test. Results Sleep efficiency was < 90% in 12/12 DM2 patients, and significantly reduced when compared with controls or with DM1. Decreased sleep efficiency was associated with sleep‐disordered breathing in seven out of 12 DM2 patients and/or periodic limbs movements of sleep (PLMS) in three out of eight patients. Six DM2 patients showed REM sleep without atonia, whereas none of the controls or DM1 patients showed REM sleep dysregulation. The global PSQI score was higher in DM2 patients than in controls and DM1 patients. Conclusions Sleep quality in DM2 patients is poorer than in DM1 patients and controls. Sleep apnea is the most common sleep disorder in DM2 patients. Obstructive sleep apnea and sleep fragmentation may represent the main cause of EDS, whereas PLMS is a frequent finding in DM1.